The potential of LEO mega-constellations in aiding GNSS to enable positioning in challenging environments - El-Mowafy, Ahmed; Wang, Kan; Allahvirdir Zadeh, Amir (2022)
Signals from the emerging Low Earth Orbit (LEO) satellites from mega-constellations that broadcast internet, such as Starlink (Space X), OneWeb, Iridium etc., also known as “signals of opportunity” (SOP), can potentially aid positioning. These LEO satellites are approximately 20 times closer to Earth compared to the GNSS medium-earth orbit (MEO) satellites – with 300-1500km altitudes, and 90-120 minutes orbital periods. Hence, LEO satellites provide a new navigation space infrastructure with much stronger signal power than GNSS signals. This makes these LEO signals more resilient to interference and available in deep attenuation settings. In challenging environments, with limited GNSS observations that may not allow positioning, such as in urban canyons, bushland, or bottom of mining pits, integrating LEO signals with the available GNSS observations can enable positioning. Moreover, the corresponding high speed of LEO satellites enables faster satellite geometry change, and hereby significantly shortens the convergence time for precise point positioning (PPP). In this contribution, the positioning from LEO Doppler shift time variation integrated with GNSS and two challenges in positioning using LEO will be briefly discussed. For positioning, the orbits of LEO satellites and their clock behaviour must be known. In addition, unlike GNSS satellites, LEO satellites are not equipped with atomic clocks, and typically use ultra-stable oscillators (USOs) or oven-controlled crystal oscillators (OCXOs), nor are they tightly time-synchronised with each other. The estimation and prediction of these orbits and clock errors and drift are discussed.